(untitled) (Revista Brasileira Multidisciplinar, 2020)
Leprosy is caused by Hansen’s bacillus, which affects the skin and peripheral nervous system. Brazil has a detection rate of 12.2 / 100 thousand inhabitants. The objective of the research was to analyze the cases of leprosy in the municipality of Votuporanga / SP, between 2014 to 2018. Data were collected from Datasus at the end of 2018. Of the 33 cases, 51, 5% were in males and 48, 5% in females, the majority between the ages of 30 and 59 (58%). The mode of entry was the predominance of new cases (76%). Routing was the most commonly used detection mode (52%); the spontaneous demand, 18%, examination of contacts, 18% and others, 12%. As to the clinical form, 34% were virchowiana, 24% dimorphic, 27% tuberculoid and 15% undetermined, thus, the Multibacillary form (58%) and the Paucibacilar form (42%) were highlighted The therapeutic regimen confirms the data already mentioned, with more prevalent MDT / MB / 12 doses (58%). The affected skin lesions and nerves were mostly ignored. The degree of disability was found to be more significant (79%), 15% had disability grade 1 and 6% were already in grade 2. The type of output with the highest percentage was the cure (70%), transfers reached 6% and 21% don’t appear in the records. The municipality studied did not reach the goal of elimination and presents many contagious forms. It is extremely important to identify and treat cases; and to invest in disability preventions.